2019
DOI: 10.1152/ajpendo.00362.2018
|View full text |Cite
|
Sign up to set email alerts
|

Systemic bile acids induce insulin resistance in a TGR5-independent manner

Abstract: Bile acids are involved in the emulsification and absorption of dietary fats, as well as acting as signaling molecules. Recently, bile acid signaling through farnesoid X receptor and G protein-coupled bile acid receptor (TGR5) has been reported to elicit changes in not only bile acid synthesis but also metabolic processes, including the alteration of gluconeogenic gene expression and energy expenditure. A role for bile acids in glucose metabolism is also supported by a correlation between changes in the metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Based on the fasting glucose and C-peptide levels, IS HOMA-cp predominantly represents hepatic insulin sensitivity [16,32], so increased fasting S-TBA levels were closely associated with blunted hepatic insulin sensitivity. Syring et al [33] documented that direct elevation of S-TBAs by BA infusion could reduce hepatic insulin sensitivity and disturb insulin levels to suppress hepatic glucose production, which supported our results. In addition, our study also showed that systemic insulin sensitivity assessed by ISI M-cp was inversely associated with fasting S-TBAs.…”
Section: Endocrine Journal Advance Publicationsupporting
confidence: 91%
See 2 more Smart Citations
“…Based on the fasting glucose and C-peptide levels, IS HOMA-cp predominantly represents hepatic insulin sensitivity [16,32], so increased fasting S-TBA levels were closely associated with blunted hepatic insulin sensitivity. Syring et al [33] documented that direct elevation of S-TBAs by BA infusion could reduce hepatic insulin sensitivity and disturb insulin levels to suppress hepatic glucose production, which supported our results. In addition, our study also showed that systemic insulin sensitivity assessed by ISI M-cp was inversely associated with fasting S-TBAs.…”
Section: Endocrine Journal Advance Publicationsupporting
confidence: 91%
“…Those defects in BA metabolism were associated with high levels of markers of total BA synthesis and defective hepatic BA transport [5], which may lead to increased S-TBA levels in peripheral circulation. Increased systemic BAs, regardless of the status of BAs (conjugation or unconjugated species), can directly induce hepatic insulin resistance and impair insulin action to inhibit hepatic glucose production [33]. However, in the portal vein, increased BAs cannot impair hepatic insulin sensitivity.…”
Section: Endocrine Journal Advance Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this, and the role of TGR5 in glucose metabolism, we hypothesised that impaired activity of this receptor contributes to glucose homeostasis in ICP, and so pregnant Tgr5 −/− mice were also studied. To our knowledge, glucose homeostasis in pregnant Tgr5 −/− mice has not previously been investigated, however it has been observed in male Tgr5 −/− mice that there was no impact on insulin action and hyperinsulinemic-euglycemic clamp studies revealed that glucose infusion rates were no different to wild type mice 43 . Our data showed that pregnant Tgr5 −/− mice were significantly glucose intolerant and had reduced insulin secretion in response to an oral glucose challenge.…”
Section: Discussionmentioning
confidence: 95%
“…FXR has also been shown to reverse insulin resistance in animal models, suggesting it may be beneficial in the treatment of T2D [ 69 ]. Interestingly, increased levels of BAs in the plasma of mice was also found to decrease insulin sensitivity through an undetermined mechanism; however, exogenous administration of insulin was found to have no effect on insulin sensitivity [ 70 ]. It may be that CDCA is improving both insulin production and diffusion within the capsules.…”
Section: Discussionmentioning
confidence: 99%